2016
DOI: 10.1136/bjsports-2016-096810
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and pregnancy in recreational and elite athletes: 2016 evidence summary from the IOC expert group meeting, Lausanne. Part 2—the effect of exercise on the fetus, labour and birth

Abstract: This is Part 2 of 5 in the series of evidence statements from the IOC expert committee on exercise and pregnancy in recreational and elite athletes. Part 1 focused on the effects of training during pregnancy and on the management of common pregnancy-related symptoms experienced by athletes. In Part 2, we focus on maternal and fetal perinatal outcomes. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 115 publications
4
57
0
1
Order By: Relevance
“…A systematic review by the 2016 Evidence summary of the International Olympic Committee expert group meeting on exercise and pregnancy in recreational and elite athletes concluded that exercise did not increase the risk of induction, epidural, episiotomy or perineal tears, and forceps or vacuum delivery, but appeared to be associated with a shorter first stage of labor and lower risk of cesarean delivery [85]. Similarly, a recent systematic review and meta-analysis concluded that based on moderate quality evidence from 20 exercise-only RCTs conducted antenatally (n = 3819), the odds of instrumental delivery in women who exercised was lower than those who did not; there were no differences between groups in any other labor/delivery variables studied [86].…”
Section: Easier Labor and Birthmentioning
confidence: 99%
“…A systematic review by the 2016 Evidence summary of the International Olympic Committee expert group meeting on exercise and pregnancy in recreational and elite athletes concluded that exercise did not increase the risk of induction, epidural, episiotomy or perineal tears, and forceps or vacuum delivery, but appeared to be associated with a shorter first stage of labor and lower risk of cesarean delivery [85]. Similarly, a recent systematic review and meta-analysis concluded that based on moderate quality evidence from 20 exercise-only RCTs conducted antenatally (n = 3819), the odds of instrumental delivery in women who exercised was lower than those who did not; there were no differences between groups in any other labor/delivery variables studied [86].…”
Section: Easier Labor and Birthmentioning
confidence: 99%
“…(based on the review of the effects of training during pregnancy on maternal and foetal perinatal outcomes in elite athletes2).

Is heavy work or strenuous exercise during pregnancy associated with premature labour, preterm birth or adverse neonatal outcomes?

What is the prevalence of, and risk factors for, the following maternal and perinatal outcomes in elite athletes, and how do these compare with estimates for the general population?

Induction of labour, prolonged labour

Epidural, analgesia

Episiotomy

Acute and elective Caesarean section

Major levator ani defects, anal sphincter tears

Birth weight, body fat, Apgar score, complications

…”
Section: Exercise Intervention Studiesmentioning
confidence: 99%
“…Part 1 focused on the effects of training during pregnancy and on the management of common pregnancy-related complaints experienced by athletes;1 Part 2 addressed maternal and foetal perinatal outcomes;2 Part 3 reviewed the implications of pregnancy and childbirth on return to exercise and on common illnesses and complaints in the postpartum period 3. Parts 1–3 are all open access papers.…”
Section: Introductionmentioning
confidence: 99%
“…Part 1 focused on the effects of training during pregnancy and on the management of common pregnancy-related complaints that may be experienced by athletes1; part 2 addressed maternal and fetal perinatal outcomes2; part 3 reviewed the implications of pregnancy and childbirth on return to exercise and on common illnesses and complaints in the postpartum period 3. Part 4 provided recommendations for future research based on parts 1 through 3 4.…”
Section: Introductionmentioning
confidence: 99%